Overnight sleep duration and obesity in 2–5 year‐old American Indian children. Issue 7 (26th April 2018) - Ingram, D. G.; Irish, L. A.; Tomayko, E. J.; Prince, R. J.; Cronin, K. A.; Parker, T.; Kim, K.; Carmichael, L.; Grant, V. M.; Sheche, J. N.; Adams, A. K.
Summary: Background: Sleep has emerged as a potentially modifiable risk factor for obesity in children. Objectives: The purpose of this investigation was to evaluate the association between overnight sleep duration and obesity among American Indian (AI) children ages 2–5 years. Methods: Data were examined from the baseline assessment of children enrolling in the Healthy Children, Strong Families study, which is a randomized lifestyle intervention trial in five diverse rural and urban AI communities nationally among children ages 2–5 years. Multivariable models were built to assess the relationship between sleep duration and BMI z ‐score while controlling for potential sociodemographic and behavioural covariates. Results: Three hundred and ninety‐eight children had sufficient data to be included in analysis. In multivariable models controlling for potential covariates, overnight sleep duration was significantly and inversely associated with BMI z ‐score ( B = −0.158, t = −1.774, P = 0.006). Similarly, when controlling for covariates, children who slept 12 or more hours had significantly lower BMI z ‐scores compared with those who slept 8 to 10 h ( P = 0.018) or less than 8 h ( P = 0.035); the difference between 12+ hours and 10 to 12‐h groups did not reach statistical significance ( P = 0.073) but supported a linear relationship between overnight sleep duration and BMI. Weekday‐to‐weekend variability in overnight sleep duration was not associated with BMI z ‐score ( B = 0.010, t = 0.206, P = 0.837). Conclusions: Overnight sleep duration is independently and inversely related to BMI z ‐score among AI children ages 2–5 years, even when controlling for important sociodemographic and obesogenic lifestyle factors. This represents the first report, to our knowledge, of sleep duration as a risk factor for obesity among AI children.